PATH-09. Liquid biopsy of cerebrospinal fluid enables detecting and monitoring ofMYC/MYCN amplification in pediatric CNS malignancies. (3rd June 2022) - Stepien, Natalia; Haberler, Christine; Furtner-Srajer, Julia; Dorfer, Christian; Czech, Thomas; Lötsch-Gojo, Daniela; Mayr, Lisa; Baumgartner, Alicia; Azizi, Amedeo A; Peyrl, Andreas; Slavc, Irene; Müllauer, Leonhard; et al.
Abstract: In the era of precision oncology, rapid molecular profiling as well as continuous monitoring of response to treatment or relapse are of increasing importance. We investigated digital droplet (dd)PCR for cerebrospinal fluid (CSF) derived cell-free (cf)DNA detection as a new method for rapid diagnosing of MYC/MYCN amplification in CNS malignancies - a patient collective with a dismal prognosis. Wet lab validated ddPCR probes for MYC were first investigated in D425 cells, a human medulloblastoma cell line with confirmed MYC amplification. Results of the methylation array of patients with stored CSF/serum samples (-80°C) were screened for patients with MYC/MYCN amplification. Five patients with medulloblastoma (group 3/4) and MYC -amplification and one patient with a diffuse glioma and MYCN -amplification were included in this study. ddPCR was performed on cfDNA isolated from CSF or serum. MYC amplification was detected by ddPCR in 28/33 (85%) CSF samples, with 4/5 negative samples being from one patient, and only one sample showing an unsuccessful analysis. MYC amplification was detectable in all longitudinal samples in 4/5 patients. 1/1 sample from the patient with MYCN amplific ation was positive in ddPCR. We were not able to detect MYC amplification in serum samples. Importantly, a turn-around time of only six hours from sample thawing/acquisition to result generation was easily achievable. Concluding, detection of MYC/MYCN -amplification in CSF by ddPCR is feasible in the clinical setting and allows for a rapid molecular diagnosis. MYC -amplification was constantly detectable in 4/5 patients with longitudinal CSF samples, which is in-line with the tumor burden our patients suffered from. Interestingly, the detectability in the patient's serum was low, presumably due to the lower percentage of cell-free tumor (ct)DNA in serum when compared to CSF. Our results render ddPCR as a promising tool for bed-side molecular diagnosis and disease monitoring.